Effects of luxury brand perceptions on brand attachment and purchase intention: A comparative analysis among consumers in China, Hong Kong and Taiwan - Te-Hsing Ku; Tzu-Ling Lin (South African Journal of Business Management, 2018)
The purpose of this study was to investigate the relationship among luxury brand perceptions (i.e. individual value, social influence and luxury brand image), luxury brand attachment and luxury brand purchase intention. In addition, the study examines the influence of antecedents on brand attachment and purchase intention among consumers in China, Hong Kong and Taiwan (i.e. the Greater China region). Using an empirical research method, the effects of luxury perceptions on brand attachment and purchase intention are tested using the partial least squares (PLS) approach to structural equation modelling. Differences in the structural relationship among subsamples were also examined by multi-group analysis to achieve a better understanding of the characteristics of different markets, thus contributing to the marketing strategy knowledge. According to the study results, antecedents, including individual value, social influence and luxury brand image, significantly influence brand attachment and purchase intention. Furthermore, the group comparisons suggest that the three subsamples have different characteristics with respect to the structural relationship. In the China subsample, brand attachment is more likely to be influenced by social influence. In comparison, Hong Kong consumers are more rational, that is, brand attachment and purchase intention are strongly influenced by consumer's perception of luxury brand image. Finally, the purchase intention of Taiwanese consumers mainly depends on the affection for the luxury brand.
Keywords: 650